APPLICATION OF INTERNATIONAL CARIES ASSESSMENT AND DETECTION SYSTEM (ICDAS-II) AND CEO-S INDEX IN CHILDREN FROM 3 TO 5 YEARS OLD OF “HONADOMANI” - Nureña- Pérez, María Isabel (2016)
Objective: This study aimed to compare the assessment of caries according to the International System for Caries Detection andAssessment (ICDAS-II) and dmf-s in children aged 3 to 5 years. Material and Methods. The sample consisted of 100 children aged 3to 5 years of age who attended the Pediatric Dental Clinic of the Hospital National Docent Madre Niño (HONADOMANI) “SanBartolomé”, during the months of October to December. Dental examinations were performed to diagnose dental caries according to thecriteria dmf-s and ICDAS-II. The data were analyzed with descriptive statistics, measures of central tendency, test of Chi squarePearson, parametrium and Spearman correlation. Results. We found a higher prevalence of caries according ICDAS-II (89%) that dmfs(75%). There was a greater number of carious lesions recorded as ICDAS- II (13,05) that dmf-s (9,11). The average number of cariesin the oral cavity was higher with ICDAS-II (15%) than with the